(untitled) (Global Journal of Management and Business Research, 2019)
This paper focused on consumer ethnocentrism and purchase intention of home-grown wheat flour among commercial bakers in Nigeria. Despite the improved wheat flour production in Nigeria recently, the majority of wheat flour consumers (commercial bakers) still prefer the foreign-grown wheat flour to the home-grown wheat flour. This preference may not be unconnected to distrust for locally made products in terms of quality. This has raised a germane question of how does ethnocentrism could influence purchase intention of home-grown wheat flour among commercial bakers in Nigeria. In order to fill this gap in literature, this study examined the nexus among consumer ethnocentrism and purchase intention of home-grown wheat flour in Nigeria. Survey research design was adopted and the unit of analysis comprised all registered commercial bakers in Anambra state, Nigeria. Purposive sampling technique was employed and questionnaire was the research instrument.